2022
DOI: 10.1016/j.cjco.2021.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Staffing Practices and Postoperative Atrial Fibrillation Among Cardiac Surgery Patients: A Multisite Cohort Study

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 54 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…Many different studies suggested that nursing staffing practice in the postoperative period (adequate staffing level, adequate skills, and educational level) are connected with lower rates of surgical mortality and lower numbers of adverse events [ 53 ]. With the better assessment of potential complications, we can assure there is adequate nurses staffing to better monitor patients [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many different studies suggested that nursing staffing practice in the postoperative period (adequate staffing level, adequate skills, and educational level) are connected with lower rates of surgical mortality and lower numbers of adverse events [ 53 ]. With the better assessment of potential complications, we can assure there is adequate nurses staffing to better monitor patients [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many different studies suggested that nursing staffing practice in the postoperative period (adequate staffing level, adequate skills, and educational level) are connected with lower rates of surgical mortality and lower numbers of adverse events [ 53 ]. With the better assessment of potential complications, we can assure there is adequate nurses staffing to better monitor patients [ 53 ]. The estimation of staffing practice with POAF occurrence is important to help hospital managers determine the number and educational degree of nurses needed for the patient after cardiac surgery procedure with the aim to reduce postoperative complications [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation